Association of different socio-economic factors with hypertension prevalence, awareness, treatment and control in India: a demographic analysis of NFHS-4 - Mukhopadhyay, Kaushik; Mukherjee, Sonali; Barkandaj, Bikramjit; Chatterjee, Chandan (International Journal of Research in Medical Sciences, 2019)
Background: National Family Health Survey (NHFS) is a periodically conducted survey, which delivers data on health and healthcare of a representative sample of households of India. Studies that have evaluated hypertension awareness, treatment and control and its association with patient level socioeconomic factors are limited in India. The objectives of this study were to determine association of demographic variables like age, sex, habitat, wealth, religion and educational status with prevalence, awareness, treatment, and control of hypertension among rural and urban subjects in different states and union territories of india from NFHS-4 data. Methods: Data of 803211 subjects were taken from NFHS survey in 36 states and union territories of india, in 2015-2016. Prevalence of hypertension and its awareness, treatment, and control status and their association with age, sex, habitat, wealth, religion and educational status were determined. Logistic regression was carried out to evaluate the impact of different predictor variables. Results: Data of 803211 subjects were taken from NFHS survey voluntarily given by them for our project, of which 565705 (70.43%) came from rural population. 103525 of them were male which comprised of 12.89% and rest 87.11% were female volunteers in 36 states and union territories of india. Hypertension prevalence, awareness, treatment and control level in India was 17.69%, 20.44%, 34.37% and 13.64% respectively. In general, these parameters were much better in urban population and in female. Although variations were observed between different study sites, they were low with poor education and wealth index. Conclusions: Hypertension awareness, treatment, and control were mostly low among the male, rural, poor and less educated individuals with large state wise variations.